If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 6x = 8 + -4x Solving 12 + 6x = 8 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 12 + 6x + 4x = 8 + -4x + 4x Combine like terms: 6x + 4x = 10x 12 + 10x = 8 + -4x + 4x Combine like terms: -4x + 4x = 0 12 + 10x = 8 + 0 12 + 10x = 8 Add '-12' to each side of the equation. 12 + -12 + 10x = 8 + -12 Combine like terms: 12 + -12 = 0 0 + 10x = 8 + -12 10x = 8 + -12 Combine like terms: 8 + -12 = -4 10x = -4 Divide each side by '10'. x = -0.4 Simplifying x = -0.4
| 8[x+6]-3x=18 | | 18(v+1)-2v=4(4v+4)-21 | | 6(7x-8)=246 | | (-4x^2y)(3x^4)(-2xy^5)= | | 3+8z-12=2z-9+z | | 8(5x-11)=112 | | 5x^2+9x-165=0 | | 10(7x+14)=490 | | 6(7x+6)=246 | | -9(v+3)+2v+7=5v+11 | | Sin^2(x)+9sin(x)+8=0 | | (2x+3)(3x^2-2x+1)= | | 6n=0.84 | | 15x-13=12x+41 | | 105-3t-32+8t-20=-72+6t-4 | | 2x+3x+3= | | -5=-3[x+11]-17 | | 7(5x-18)=259 | | 3(2x-9)=4(x+1) | | y=20+.9x | | 3(4.32x)+3.41y=65.48 | | 5/13=9/x | | 10(6x+2)=560 | | 3(4.32x)+3.41x=65.48 | | 1/13y=65 | | x=20+.9y | | y(y-4)=0 | | 6(x-9)=234 | | 90+51=180 | | c+51=10 | | 3x^4-192x= | | x/10-6=-3 |